Commercial Law Review and Legal Politics Related To The Investment Value Gap of Apple Between Indonesia and Vietnam - Nomensen Freddy Siahaan; Agustina Wati; Ine Ventyrina (International Journal Labs, 2025)
This study employs normative legal research methods, which focus on analyzing legal norms and regulations relevant to the research topic. Normative legal research is a scientific procedure aimed at discovering the truth through logical reasoning based on the established principles of law. This method relies on the systematic examination of legal materials, including legislation, case law, and legal doctrines, to provide a comprehensive understanding of the issue under study. The data used in this study are primarily secondary in nature, consisting of laws, regulations, legal precedents, and scholarly legal commentaries that are pertinent to the topic of Commercial Law dan Political Law. Once the relevant legal materials were collected, the data analysis process began with the systematic interpretation of legal texts, focusing on their application to sexual violence and commercial law. This included evaluating the purpose, scope, and application of laws, as well as identifying any inconsistencies or gaps. A comparative legal analysis was also employed, where necessary, to contrast Indonesian laws with international conventions and legal practices from other countries, highlighting differences and suggesting improvements. Finally, the findings were synthesized to propose recommendations for enhancing legal protections against sexual violence and human trafficking. This detailed methodological approach ensures that the research is grounded in thorough legal analysis, enabling readers to understand the steps taken to collect and interpret the data without needing to refer to external sources.